Stochastic Revealed Preference and Rationalizability - Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper explorers rationalizability issues for finite sets of observations of stochastic choice in the framework introduced by Bandyopadhyay et al. (JET, 1999). Is is argued that a useful approach is to consider indirect preferences on budgets instead of direct preferences on commodity bundles. Stochastic choices are rationalizable in terms of stochastic orderings on the normalized price space if and only if there exits a solution to a linear feasibility problem. Together with the weak axiom of stochastic revealed preference the existence of a solution implies rationalizability in terms of stochastic orderings on the commodity space. Furthermore it is shown that the problem of finding sufficiency conditions for binary choice probabilities to be rationalizable bears similarities to the problem considered here.
Keywords: D11; 330; Stochastic choice; rationalizability; revealed preference; weak axiom of stochastic revealed preference; revealed favorability; Offenbarte Präferenzen; Konsumtheorie; Stochastischer Prozess; Theorie